2010
DOI: 10.4025/actasciagron.v32i3.4694
|View full text |Cite
|
Sign up to set email alerts
|

Estresse hídrico com diferentes osmóticos em sementes de feijão e expressão diferencial de proteínas durante a germinação

Abstract: RESUMO.O feijão (Phaseolus vulgaris L.) é de grande expressão alimentícia. A emergência da cultura é dependente de água e considerada a fase mais crítica. Os objetivos deste trabalho foram simular a deficiência de água no início da germinação em laboratório, em sementes de feijão 'Pérola', utilizando-se: manitol, CaCl 2 , MgCl 2 e NaCl em potenciais de 0; -0,3; -0,6; -0,9 e -1,2 MPa, estabelecidos pela equação de Van't Hoff e avaliar o perfil eletroforético de proteínas totais solúveis por meio de SDS-PAGE. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
1
5
0
2
Order By: Relevance
“…Reduction in the osmotic potential to -0.4 MPa drastically affected radicle development in cowpea seedlings, causing declines of 61.66 and 66.85% in root length and root dry matter accumulation, respectively ( Figures 1B and D). In the germination of Phaseolus vulgaris under water stress, Coelho et al (2010), Garcia et al (2012) and Carvalho et al (2013) observed that the reduction in osmotic potential substantially reduced root development and, consequently, phytomass accumulation. These authors attributed this effect to the decrease in seed hydration, since water constitutes the matrix for the occurrence of biochemical and physiological processes, which culminate in radicle protrusion.…”
Section: Dmentioning
confidence: 99%
“…Reduction in the osmotic potential to -0.4 MPa drastically affected radicle development in cowpea seedlings, causing declines of 61.66 and 66.85% in root length and root dry matter accumulation, respectively ( Figures 1B and D). In the germination of Phaseolus vulgaris under water stress, Coelho et al (2010), Garcia et al (2012) and Carvalho et al (2013) observed that the reduction in osmotic potential substantially reduced root development and, consequently, phytomass accumulation. These authors attributed this effect to the decrease in seed hydration, since water constitutes the matrix for the occurrence of biochemical and physiological processes, which culminate in radicle protrusion.…”
Section: Dmentioning
confidence: 99%
“…A special group of HSPs, the chaperones, has also been found in this molecular weight range and are involved in maintaining protein homeostasis, recovering damaged proteins, preventing, maintaining or renaturing denatured proteins (Dahiya & Buchner, 2019), important functions in cells that have been subjected to thermal stresses (Borges & Ramos, 2005). Other authors related the expression of bands in the 65, 45, 25 and 18 kDa ranges to responses to other stress types, such as the water stress (Coelho et al, 2010a).…”
Section: /7mentioning
confidence: 99%
“…A disponibilidade hídrica e o movimento da água para as sementes são importantes para a germinação e emergência das plântulas, e desse modo, são fatores influenciados pelo potencial hídrico do solo (KAPPES et al, 2009). Nem sempre o solo oferece um ambiente ótimo para a germinação das sementes e uma das condições por vezes encontrada é a pouca disponibilidade de água logo após a semeadura (Coelho et al, 2010). Nessa condição, o solo apresenta potenciais hídricos que dificultam a absorção da água necessária para a germinação das sementes (MACHADO NETO et al, 2006), o que configura o estresse hídrico logo após o plantio como um dos fatores abióticos que mais influência no processo germinativo, interferindo na atividade enzimática da planta (GARCIA et al, 2012).…”
Section: Introductionunclassified